2011
DOI: 10.1111/j.1439-0272.2011.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of aphrodisiac activity in male rats by ethanol extract of Kaempferia parviflora and exercise training

Abstract: This study aimed to investigate the effects of Kaempferia parviflora extract (KD) and exercise training on reproductive function in male rats. Sexually mature males were assigned to four groups: control, KD70 (received 70 mg kg(-1) day(-1) for 4 weeks), Ex (exercise training for 4 weeks), Ex + KD70 (exercise training with KD 70 mg kg(-1) day(-1)). At the end of treatment regimes, sexual behaviours including mount latency (ML), mount frequency (MF), ejaculation latency (EL), post-ejaculation latency (PEL), numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…KP treatment significantly increased serum testosterone levels and enhanced sexual behaviour in STZ‐induced diabetic rats. This is in line with other studies, which reported that KP treatment in male rats enhances sexual motivation (Chaturapanich et al., ) and that KP treatment in normal rats at 240 mg/kg led to a reduction in the time associated with courtship behaviour in the first 10 min (Sudwan et al., ). More recent research has show that the effect of KP to enhance sexual performance by increasing blood flow to the testis, enhancing NO production in medial pre‐optic area (MPOA) results, is complex sexual behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…KP treatment significantly increased serum testosterone levels and enhanced sexual behaviour in STZ‐induced diabetic rats. This is in line with other studies, which reported that KP treatment in male rats enhances sexual motivation (Chaturapanich et al., ) and that KP treatment in normal rats at 240 mg/kg led to a reduction in the time associated with courtship behaviour in the first 10 min (Sudwan et al., ). More recent research has show that the effect of KP to enhance sexual performance by increasing blood flow to the testis, enhancing NO production in medial pre‐optic area (MPOA) results, is complex sexual behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…More recent research has show that the effect of KP to enhance sexual performance by increasing blood flow to the testis, enhancing NO production in medial pre‐optic area (MPOA) results, is complex sexual behaviour. Furthermore, the same study shows that 7‐methoxyflavone had an inhibitory activity against phosphodiesterase 5 (PDE5) (Chaturapanich et al., ; Chaturapanich et al., ; Temkitthawon et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that alcohol extract had an aphrodisiac activity probably via a marked increase in blood flow to the testis. In another study, Chaturapanich, Chaiyakul, Verawatnapakul, Yimlamai, and Pholpramool () investigated the effects of K. parviflora extract (KD) and exercise training on reproductive function in male rats. They observed that the weights of epididymis, seminal vesicles, prostate gland and levator ani muscle were significantly increased in the exercise training with the extract treated group.…”
Section: Medicinal Plants Andplant‐derived Products Used As Aphrodisimentioning
confidence: 99%
“…Kaempferia parviflora belongs to the Zingiberaceae family and has been used as a folk medicine and food in Thailand (Nakao et al., ). The extracts of K. parviflora rhizomes have various biological activities including: (a) inhibitory effects on P‐glycoprotein function (Patanasethanont et al., ); (b) anti‐plasmodial, anti‐fungal, and anti‐mycobacterial activities (Yenjai, Prasanphen, Daodee, Wongpanich, & Kittakoop, ); (c) cytotoxic effect on cancer cells (Yenjai & Wanich, ); (d) anti‐cholinesterase activity (Sawasdee, Sabphon, Sitthiwongwanit, & Kokpol, ); (e) anti‐allergic activity (Tewtrakul, Subhadhirasakul, & Kummee, ); (f) suppressive effect on the function of multidrug resistance‐associated protein; (g) anti‐gastric ulcer effect (Rujjanawate, Kanjanapothi, Amornlerdpison, & Pojanagaroon, ); (h) anti‐obesity effect (Akase et al., ); (i) aphrodisiac activity (Chaturapanich, Chaiyakul, Verawatnapakul, Yimlamai, & Pholpramool, ); and (j) enhancing effects on ATP production and glucose uptake in skeletal muscle cells (Toda et al., ). At least ten methoxyflavone derivatives (six 5,7‐dimethoxyflavone (DMF) derivatives and four 5‐hydroxy‐7‐methoxyflavone (HMF) derivatives) have been isolated from K. parviflora (Nakao et al., ).…”
Section: Introductionmentioning
confidence: 99%